EDITORIAL - Phongsatha, Thanawan (Journal of Interdisciplinary Research (ISSN: 2408-1906), 2025)
The Journal of Interdisciplinary Research (JIR) is a tri-annual international publication dedicated to disseminating high-quality, peer-reviewed scholarship in the field of Social Sciences. Serving as a platform for academic dialogue, the journal fosters the exchange of ideas and the advancement of research across a wide range of disciplines. JIR is officially indexed in the Thai Citation Index (TCI), Tier 2, and operates as an open-access journal with the primary goal of encouraging meaningful academic collaboration among researchers, scholars, and students from diverse backgrounds. Its mission is to provide a hub for interdisciplinary conversations and knowledge sharing that address emerging trends and pressing issues in the global academic landscape. This volume presents 19 exceptional articles authored by researchers from various countries and academic institutions. Employing diverse methodologies—quantitative, and mixed-method approaches—the contributions explore themes such as educational leadership, educational technology, technology-enhanced teaching, management, and learning processes. The breadth of perspectives reflects the journal’s commitment to cross-cultural, multi-contextual, and interdisciplinary scholarship. We extend our deepest gratitude to all contributing authors for their dedication to advancing knowledge that benefits society and enriches scholarly inquiry. Moving forward, the Journal of Interdisciplinary Research (JIR) remains committed to supporting the academic community by publishing impactful research and fostering dialogue across disciplines. We warmly welcome submissions that align with the journal’s vision of promoting interdisciplinary scholarship and addressing complex challenges through collaborative research. Assistant Professor Dr.Thanawan Phongsatha Editor-in-Chief Journal of Interdisciplinary Research (JIR)